Faktor Determinan Kejadian Hipertensi di Desa Sikeben Kecamatan Sibolangit Kabupaten Deli Serdang - Imam El Islamy; Liyana Simamora; Alfiya Syahri; Nurlayla Zaini; Nur Ainun Sagala; Anggrainy Dwi (Universitas Batanghari Jambi, 2023)
Hypertension is an increase in systolic and diastolic blood pressure above normal levels. In Indonesia, the prevalence of hypertension based on the results of measurements in the adolescent to elderly population is 34.1% to 55.2%. Factors causing hypertension consist of primary hypertension and secondary hypertension. This study aims to determine the risk factors for hypertension that occur in the community in Sikeben Village, Sibolangit Regency, Deli Serdang District in 2022. The type of research used is quantitative with descriptive analytic methods and uses a cross sectional approach. Intake of respondents with purposive sampling technique as many as 64 respondents with an age range of 18 years and over. The statistical test in analyzing the research data uses the Chi-square method. The results of this study indicate that there is a relationship between age (p-value=0.005), smoking history (p-value=0.014), and Body Mass Index (BMI) (p-value=0.004) with the incidence of hypertension in Sikeben Village, Sibolangit District , Deli Serdang District in 2022. It is hoped that people can stop smoking and reduce their body mass, so that people can reduce the incidence of hypertension and can improve public health status.